PENGARUH REKRUTMEN DAN PENGALAMAN KERJA TERHADAP PRESTASI KERJA DENGAN PENEMPATAN KERJA SEBAGAI VARIABEL INTERVENING - Qhifari Zaka Wali; Hadi Sunaryo; Pardiman Pardiman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study aims to determine the effect of recruitment and work experience on work performance with work placement as an intervening variable in the Ramayana City of Malang Population and samples of employees as many as 57 respondents. In this study the data collection techniques used were questionnaires and interviews. The tool used for data analysis in this study is to use a software application in the form of SPSS version 20. The analysis method in this study uses path analysis. The instrument test in this study was a normality test, reliability test, validity test, t test, Sobel test. The results of the analysis show that Recruitment and Work Experience have a direct effect on Employee Work Placement, Recruitment and Work Experience have a direct effect on Employee Job Performance, Work Placement has an effect on Employee Performance, Recruitment has an indirect effect on Job Performance through Job Placement.Keywords: Recruitment, Work Experience, Job Performance, Job Placement